DEFINITION pc3_gen_lift()
TYPE =
∀c:C
.∀t1:T
.∀t2:T
.∀h:nat
.∀d:nat.(pc3 c (lift h d t1) (lift h d t2))→∀e:C.(drop h d c e)→(pc3 e t1 t2)
BODY =
assume c: C
assume t1: T
assume t2: T
assume h: nat
assume d: nat
suppose H: pc3 c (lift h d t1) (lift h d t2)
assume e: C
suppose H0: drop h d c e
(H1) consider H
consider H1
we proved pc3 c (lift h d t1) (lift h d t2)
that is equivalent to ex2 T λt:T.pr3 c (lift h d t1) t λt:T.pr3 c (lift h d t2) t
we proceed by induction on the previous result to prove pc3 e t1 t2
case ex_intro2 : x:T H2:pr3 c (lift h d t1) x H3:pr3 c (lift h d t2) x ⇒
the thesis becomes pc3 e t1 t2
(H4)
by (pr3_gen_lift . . . . . H3 . H0)
ex2 T λt2:T.eq T x (lift h d t2) λt2:T.pr3 e t2 t2
end of H4
we proceed by induction on H4 to prove pc3 e t1 t2
case ex_intro2 : x0:T H5:eq T x (lift h d x0) H6:pr3 e t2 x0 ⇒
the thesis becomes pc3 e t1 t2
(H7)
by (pr3_gen_lift . . . . . H2 . H0)
ex2 T λt2:T.eq T x (lift h d t2) λt2:T.pr3 e t1 t2
end of H7
we proceed by induction on H7 to prove pc3 e t1 t2
case ex_intro2 : x1:T H8:eq T x (lift h d x1) H9:pr3 e t1 x1 ⇒
the thesis becomes pc3 e t1 t2
(H10)
we proceed by induction on H8 to prove eq T (lift h d x1) (lift h d x0)
case refl_equal : ⇒
the thesis becomes the hypothesis H5
eq T (lift h d x1) (lift h d x0)
end of H10
(H11)
by (lift_inj . . . . H10)
we proved eq T x1 x0
we proceed by induction on the previous result to prove pr3 e t1 x0
case refl_equal : ⇒
the thesis becomes the hypothesis H9
pr3 e t1 x0
end of H11
by (pc3_pr3_t . . . H11 . H6)
pc3 e t1 t2
pc3 e t1 t2
pc3 e t1 t2
we proved pc3 e t1 t2
we proved
∀c:C
.∀t1:T
.∀t2:T
.∀h:nat
.∀d:nat.(pc3 c (lift h d t1) (lift h d t2))→∀e:C.(drop h d c e)→(pc3 e t1 t2)